Morphology, morphometry and ultrastructure of the Amazonian manatee (Sirenia: Trichechidae) spermatozoa - Amaral, Rodrigo de Souza (2010)
This study describes the morphological, morphometric and ultrastructural characteristics of the Amazonian manatee Trichechus inunguis (Natterer, 1883) spermatozoon. The spermatozoa were obtained from a urine sample of an adult T. inunguis kept in captivity. The spermatozoa were analyzed by light and transmission electron microscopy. The head of Amazonian manatee spermatozoa had a flat oval shape and a well distinguishable midpiece. The mean dimensions of the spermatozoa were: head length, 7.49 ± 0.24 µm; head width, 3.53 ± 0.19 µm; head thickness, 1.61 ± 0.13 µm; midpiece length, 11.36 ± 0.34 µm; flagellum length, 40.91 ± 1.94 µm; total tail length, 52.16 ± 1.06 µm; total spermatozoon length, 60.08 ± 1.40 µm. The Amazonian manatee spermatozoa were similar in shape to other sirenian spermatozoa; however, presenting a different size. This study describes, for the first time, the morphometric and ultrastructural characteristics of the Amazonian manatee spermatozoa, and also demonstrates the possible use of spermatozoa retrieved from urine samples for biological studies.